2023
DOI: 10.1111/jvim.16668
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional electro‐anatomical mapping and radiofrequency ablation as a novel treatment for atrioventricular accessory pathway in a horse: A case report

Abstract: We describe the diagnosis and treatment of an atrioventricular accessory pathway (AP) in a horse using 3‐dimensional electro‐anatomical mapping (3D EAM) and radiofrequency catheter ablation (RFCA). During routine evaluation of the horse, intermittent ventricular pre‐excitation was identified on the ECG, characterized by a short PQ interval and abnormal QRS morphology. A right cranial location of the AP was suspected from the 12‐lead ECG and vectorcardiography. After precise localization of the AP using 3D EAM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In human medicine, radiofrequency ablation would have been used to treat the underlying cause of the AF. Although this technology has not yet been fully developed in horses, the treatment of other arrhythmias, such as sustained atrial tachycardia and an accessory pathway, has been reported (Buschmann et al, 2023; Phillips et al, 2022; Van Steenkiste et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, radiofrequency ablation would have been used to treat the underlying cause of the AF. Although this technology has not yet been fully developed in horses, the treatment of other arrhythmias, such as sustained atrial tachycardia and an accessory pathway, has been reported (Buschmann et al, 2023; Phillips et al, 2022; Van Steenkiste et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 3D electroanatomical mapping followed by radiofrequency ablation is a promising tool for arrhythmia treatment as this therapy also deals with the underlying causal mechanism and thus reduces the risk for recurrence (van Loon et al., 2020). Successful ablation has been described for focal and macro‐re‐entrant AT (Van Steenkiste et al., 2022) and for an atrioventricular accessory pathway (Buschmann et al., 2023). For horses with AF, electroanatomical mapping and ablation therapy could potentially be useful to reduce the arrhythmogenic substrate, especially in those horses which present focal or macro‐re‐entrant AT as the underlying mechanism.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…[5][6][7][8] Mapping of the whole heart was performed in 2020, 9 and mapping and radiofrequency ablation of atrial tachycardia and an accessory pathway was also described earlier. 10,11 However, the available information on anatomical, histological and immunohistochemical assessment of the pulmonary vein ostia and the conduction system of the myocardial sleeve is still obscure in this species. [12][13][14] After the common pulmonary vein is canalised during human heart development, it attaches to the left atrium initially with one single orifice.…”
Section: Introductionmentioning
confidence: 99%